(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
When we talk about the life of a creative person, a person and his heart, deep observations of pure, sincere and unique feelings, fluency in style, new, original artistic thinking, harmony of form and content, high artistic criteria, we witness that the tender feelings we receive in the pen find their high expression in the poetry of Matnazar Abdulhakim, and that the love lyric has a special significance in the poet’s work.